Seizure presentation and incidence-associated factors in treated cerebral arteriovenous malformations: a secondary analysis of the MISTA consortium - Sconzo, Daniel; Ramirez-Velandia, Felipe; Muram, Sandeep; Enriquez-Marulanda, Alejandro; Adeeb, Nimer; Kandregula, Sandeep; Salim, Hamza Adel; Musmar, Basel; Dmytriw, Adam A.; Kondziolka, Douglas; Naamani, Kareem El; Sheehan, Jason; et al. (Neurosurgical review, 2025)
Seizures occur in 20-45% of patients with cerebral arteriovenous malformations (AVMs) and can potentially influence their quality of life. Some studies have suggested risk factors influencing their development, but the evidence is limited to small cohorts. To analyze seizure presentation and factors influencing seizure development in patients with cerebral AVMs using a multi-institutional consortium. Retrospective multicenter registry from multiple centers in North America and Europe of patients aged 1 to 89 years who had undergone any intervention for brain AVMs between January 2010 and December 2023. Demographics, functional assessment (modified Rankin Scale; mRS), and AVM characteristics, were evaluated to assess for relationship with seizures using a multivariate generalized linear mixed-effects model. 1,005 AVM patients were analyzed; the median age was 42, 73% had a baseline mRS ≤ 2. The median nidus size was 2.2 cm, and most AVMs were Spetzler-Martin grade II (37%). Seizure was the presenting symptom in 237 patients (24%). After adjusting for significant variables, patient-specific factors associated with seizures were younger age (OR 0.99, CI95% 0.98-1), male sex (OR 1.65, CI95% 1.18-2.30), and smoking history (OR 1.69, CI95% 1.17-2.44). AVM-specific factors associated with seizures included rupture status (OR 0.42, CI95% 0.30-0.61); eloquent cortex (OR 1.61, CI95% 1.13-2.29); frontal (OR 1.54, CI95% 1.01-2.35), temporal (OR 1.93, CI95% 1.26-2.96) and parietal (OR 1.71 CI95% 1.08-2.71) location; larger nidal size (OR = 1.23, CI95% 1.08-1.39), and superficial draining vein location (OR 1.86, CI95% 1.15-3.01). In this multicenter consortium, after controlling for significant variables, the incidence of AVM-related seizures was associated with younger age, male sex, smoking history, larger AVMs, eloquent locations, and AVMs in the frontal, temporal, and parietal cortices. Conversely, rupture status, deep venous drainage, and cerebellar locations were negatively associated with seizures.